2011
DOI: 10.2350/10-09-0902-oa.1
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Expression of Embryonic Stem Cell Markers in Malignant Rhabdoid Tumors

Abstract: Malignant rhabdoid tumor is a highly aggressive pediatric neoplasm molecularly characterized by inactivating mutations of the SMARCB1 gene, a potent tumor suppressor and member of the SWI/SNF chromatin remodeling complex. It has been suggested that oncogenesis in SMARCB1-deficient cancers, such as malignant rhabdoid tumors, is driven not by the loss of SWI/SNF function but by an aberrant functioning of the BRG1-containing SWI/SNF complex. Since Brg1 is required for self-renewal and pluripotency of mouse embryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
43
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 47 publications
6
43
2
Order By: Relevance
“…In yolk sac tumors and primary extragonadal germ cell tumors, one study reported that the circulating tumor cells are detectable by anti-SALL4 antibody in peripheral blood samples, making this protein a more sensitive marker than α-fetoprotein and glypican-3 107 . In addition, SALL4 is expressed in a majority of malignant rhabdoid tumors (MRTs) 20108109110111 but rarely expressed in epithelioid sarcomas. Therefore, SALL4 immunoexpression may be a useful diagnostic tool to distinguish epitheloid sarcoma from malignant rhabdoid tumor.…”
Section: Sall4 In Cancersmentioning
confidence: 99%
“…In yolk sac tumors and primary extragonadal germ cell tumors, one study reported that the circulating tumor cells are detectable by anti-SALL4 antibody in peripheral blood samples, making this protein a more sensitive marker than α-fetoprotein and glypican-3 107 . In addition, SALL4 is expressed in a majority of malignant rhabdoid tumors (MRTs) 20108109110111 but rarely expressed in epithelioid sarcomas. Therefore, SALL4 immunoexpression may be a useful diagnostic tool to distinguish epitheloid sarcoma from malignant rhabdoid tumor.…”
Section: Sall4 In Cancersmentioning
confidence: 99%
“…The immature phenotype of MRT, expression of many transcription factors and markers associated with stem cell networks, and the potential of MRT cells to differentiate to some degree along various lineages have been reported (11)(12)(13). In particular, SMARCB1 is required in the SWI/SNF chromatin remodeling complex for controlling the differentiation potential of MRT cells (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Even though SALL4 is a highly specific marker for a broad spectrum of germ cell tumors, its expression has been reported in 89% of hepatoid gastric carcinomas, 95 58% of embryonal components of hepatoblastoma, 89 88% of malignant rhabdoid tumors, and 50% of Wilms tumors. 208,209 More recently, a unique punctate/ clumped nuclear staining pattern of SALL4 was observed in 30 of 32 HCCs (94%). 88 This staining pattern tended to be focal (,25% of the tumor cells stained) when compared with the diffuse nuclear staining in yolk sac tumors.…”
mentioning
confidence: 99%